1997
DOI: 10.1002/(sici)1097-0061(19970615)13:7<677::aid-yea131>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of aCandida albicans Gene (SSB1) Coding for a Protein Related to the Hsp70 Family

Abstract: We have cloned and sequenced a Candida albicans gene (SSB1) encoding a potential member of the heat‐shock protein seventy (hsp70) family. The protein encoded by this gene contains 613 amino acids and shows a high degree (85%) of sequence identity to the ssb subfamily (ssb1 and ssb2) of the Saccharomyces cerevisiae hsp70 family. The transcribed mRNA (2·1 kb) is present in similar amounts both in yeast and germ tube cells of C. albicans. The sequence data has been deposited in the GenBank data library under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Details of RNA preparation and cDNA synthesis have been published previously (Felk et al, 2002). For an internal mRNA control and for detection of genomic DNA, we used EFB1 (Maneu et al, 1996). The DNA amplification fragment contained a 364 bp intron.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of RNA preparation and cDNA synthesis have been published previously (Felk et al, 2002). For an internal mRNA control and for detection of genomic DNA, we used EFB1 (Maneu et al, 1996). The DNA amplification fragment contained a 364 bp intron.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of these cells were separated from the mucosal equivalent during the fixation and embedding process due to a reduced adherence. To rule out lower RNA levels isolated from these samples as the reason for the altered SAP expression profiles, we amplified the cDNA of the C. albicans EFB1 gene (Maneu et al, 1996), which is expressed in living C. albicans cells to a similar extent under all conditions and is therefore a useful internal standard (Schaller et al, 1998(Schaller et al, , 1999. Similar expression levels of EFB1 relative to the same amount of total RNA used in each RT-PCR experiment suggested that all strains were growing on the RHE tissue (Fig.…”
Section: Mutants Lacking Efg1 Have Attenuated Abilities To Damage Epimentioning
confidence: 99%
“…The CaMAL2 promoter region was amplified using the MalPr-5h\MalPr-3h primers as follows : initial denaturation for 3 min at 94 mC followed by three-step cycling of 30 s denaturation at 94 mC, 30 s annealing at 57 mC, 30 s extension at 72 mC and 5 min final extension at 72 mC. The 3h untranslated region (3hUTR) of the gene encoding C. albicans elongation factor EF-1β (CaEFB1) (Maneu et al, 1996) was amplified using the same conditions with EFB1\3hU-5h and EFB1\3hU-5h primers. To ensure that the whole 3hUTR of CaEFB1 was present we amplified a 538 bp DNA fragment instead of the 253 bp fragment described by Maneu et al (1996).…”
Section: Methodsmentioning
confidence: 99%
“…The 3h untranslated region (3hUTR) of the gene encoding C. albicans elongation factor EF-1β (CaEFB1) (Maneu et al, 1996) was amplified using the same conditions with EFB1\3hU-5h and EFB1\3hU-5h primers. To ensure that the whole 3hUTR of CaEFB1 was present we amplified a 538 bp DNA fragment instead of the 253 bp fragment described by Maneu et al (1996). Engineered human salivary histatin genes .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation